2017
DOI: 10.1136/bcr-2017-219422
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic myositis ossificans circumscripta (MOC)

Abstract: We report a case of a 29-year-old man who had been a victim of a public road accident. Four weeks later, the patient developed an isolated right thigh mass located ventrally in the distal one-third of the thigh. The mass was painful and associated with fever and inflammatory syndrome. Plain radiographs showed a bilateral calcified thickening of soft tissues with well-defined bony margins. Ultrasound objectified diffuse calcifications of soft tissues.CT scan-confirmed the diagnosis of myositis ossificans circum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…Traumatic MO accounts for approximately 75% of cases, while the other 25% consists of neurogenic, congenital, and idiopathic MO. [4,14] According to the hereditary, severity of diffuse heterotopic ossification, and underlying causes, MO can be divided into 3 types [15] : MOC, MO progressiva (fibrodysplasia ossificans progressive), and MO without a history of trauma or pseudo-malignant MO (non-traumatic MO). The last one includes cases associated with burns, polio, paraplegia, hemophilia, or infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traumatic MO accounts for approximately 75% of cases, while the other 25% consists of neurogenic, congenital, and idiopathic MO. [4,14] According to the hereditary, severity of diffuse heterotopic ossification, and underlying causes, MO can be divided into 3 types [15] : MOC, MO progressiva (fibrodysplasia ossificans progressive), and MO without a history of trauma or pseudo-malignant MO (non-traumatic MO). The last one includes cases associated with burns, polio, paraplegia, hemophilia, or infections.…”
Section: Discussionmentioning
confidence: 99%
“…[2] More than 80% of lesions occur within the large muscles of the extremities, especially in the girdles and thighs. The affected muscles in published cases included: iliopsoas, [3] triceps brachii, [2] quadriceps femoris, [4][5][6] biceps femoris, [7,8] tibialis anterior, [9] paravertebral, [10] buccinators, [11] masseter, [12,13] etc. To the best of our knowledge, cases of MOC involving the pectineus muscle are rare, [7] and no reported cases have been treated surgically.…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic myositis ossificans (MO) circumscripta is an inflammatory disorder that arises in skeletal muscle [1]. It is a benign, solitary, self-limiting disorder representing metaplasia of bone.…”
Section: Introductionmentioning
confidence: 99%
“…Kan et al [3] demonstrated that the cellular mechanism of heterotopic bone formation is the result of the dysregulation of local stem cells in response to tissue injury and inflammation. Men and women are equally affected with no preferential anatomical site, though clinical cases in the girdles and limbs are frequently described [1].…”
Section: Introductionmentioning
confidence: 99%